Factors determining acceptance of disease and its impact on satisfaction with life of patients with peripheral artery disease - Renata Piotrkowska; Sylwia Terech‐Skóra; Wioletta Mędrzycka‐Dąbrowska; Piotr Jarzynkowski; Magdalena Król (Wiley, 2021)
Abstract Aims and objectives Analysis of factors determining acceptance of disease and satisfaction with life in patients with peripheral artery disease. Background Peripheral artery disease is more common in older patients and is associated with increased morbidity and mortality due to cardiovascular diseases and the risk of amputation. The acceptance of disease is one of the most important factors for adjusting to life with a chronic disease. Design A cross‐sectional survey study. Patients' questionnaires. Method The participants were patients with peripheral artery disease (N = 72). The study included the use the standardized research tools the Acceptance of Illness Scale (AIS) and the Satisfaction with Life Scale (SWLS). Results The highest acceptance of disease was observed for patients with higher education, while the lowest was found for patients with the greatest limitation of physical mobility. Conclusions The education level and physical fitness of patients had significant impact on disease acceptance.